Role of Guava to National Economy of Bangladesh: An Empirical Study - Hossen , Sayed Mohibul (Global Disclosure of Economics and Business, 2013)
Guava, which is a very delicious fruit, is rich in vitamin C and contains the appreciable amount of vitamin A too. It is also a good source of pectin –a dietary fiber. Different types of favorite dishes are made from guava such as guava jelly, guava syrup, guava cheese, guava roll, etc. Many countries export these types of foods and earn a lot of foreign money. Although Bangladesh is one of the best producers, there is no industry for preserving this fruit. So, all the production become indeed in consumption.The aim of the research is to know the cultural practices of guava in Bangladesh and how to make sweetened guava dishes which can play a vital role to our economy and to identify the best model that may be used for forecasting purposes. The present study attempts to do a statistical analysis of current guava production and its prospect in Bangladesh by considering the various sources of variations on the time-series data for 23 districts of Bangladesh and over a period of 27 years (1981-82 to 2007-08). The study was considered for whole Bangladesh. JEL Classification Code: E01; E20